Three-arm polyrotaxanes with multidirectional molecular motions as the nanocarrier for nitric oxide-enhanced photodynamic therapy against bacterial biofilms in septic arthritis - Shixin Liu; Yuanfang Jiang; Yu Zhang; Kai Lv; Jiaxin Zhu; Mei Liu; Hao Xu; Genlong Jiao; Wanyong Yang; Guodong Sun; Dong Ma (Journal of Nanobiotechnology)
Abstract Bacterial biofilms are one of the major contributors to the refractoriness of septic arthritis. Although nitric oxide (NO)-enhanced photodynamic (PDT) therapy has been involved in biofilm eradication, the anti-biofilm efficacy is usually hindered by the short half-life and limited diffusion distance of active molecules. Herein, we report a three-arm structure using the photosensitive core chlorin e6 to integrate three α-cyclodextrin (α-CD) polyrotaxane chains as the supramolecular nanocarrier of NO-enhanced PDT therapy, in which NO was loaded on the cationic rings (α-CDs). Beneficial from the enhanced permeability of the nanocarrier due to the collective act on biofilms by the molecular motions (slide and rotation of rings) of three chains in different directions, NO capable of inducing biofilm dispersal and reactive oxygen species were efficiently delivered deep inside biofilms under 660 nm laser irradiation, and reactive nitrogen species with stronger bactericidal ability was produced in-situ, further accomplishing bacteria elimination inside biofilms. In-vivo therapeutic performance of this platform was demonstrated in a rat septic arthritis model by eliminating the methicillin-resistant Staphylococcus aureus infection, and potentiating the immune microenvironment regulation and bone loss inhibition, also providing a promising strategy to numerous obstinate clinical infections caused by biofilms. Graphical Abstract